The Impact of Quarantine and Physical Distancing Following COVID-19 on Mental Health: Study Protocol of a Multicentric Italian Population Trial - Giallonardo, Vincenzo; Sampogna, Gaia; Del Vecchio, Valeria; Luciano, Mario; Albert, Umberto; Carmassi, Claudia; Carrà, Giuseppe; Cirulli, Francesca; Dell’Osso, Bernardo; Nanni, Maria Giulia; Pompili, Maurizio; Sani, Gabriele; et al. (Frontiers in Psychiatry, 2020)
The COVID-19 pandemic and its related containment measures are having detrimental consequences on the mental health of the general population worldwide. In particular, frustration, loneliness and worries about the future are common reactions and represent well-known risk factors for several mental disorders, including anxiety, affective and post-traumatic stress disorders. The vast majority of available studies have been conducted in China, where the pandemic started. Italy has been severely hit by the pandemic, and the socio-cultural context is completely different from Eastern countries. Therefore, there is the need for methodologically rigorous studies aiming to evaluate the impact of COVID-19 and quarantine measures on the mental health of the Italian population. In fact, our results will help us to develop appropriate interventions for managing the psychosocial consequences of pandemic. The “COVID-IT-mental health trial” is a no-profit, not-funded, national, multicentric, cross-sectional population-based trial aiming: a) to evaluate the impact of COVID-19 pandemic and its containment measures on mental health of the Italian population; b) to identify the main areas to be targeted by supportive long-term interventions for the different categories of people exposed to the pandemic. Data will be collected through a web-platform using validated assessment tools. Participants will be subdivided into four groups: a) Group 1 - COVID-19 quarantine group. This group includes the general population which are quarantined but not isolated – i.e., those not directly exposed to contagion nor in contact with COVID-19+ individuals; b) Group 2 - COVID-19+ group, which includes isolated people directly/indirectly exposed to the virus; c) Group 3 - COVID-19 healthcare staff group, which includes first- and second-line healthcare professionals; d) Group 4 - COVID-19 mental health, which includes users of mental health services and all those who had already been diagnosed with a mental disorder. Mental health services worldwide are not prepared yet to manage the short- and long-term consequences of the pandemic. It is necessary to have a clear picture of the impact that this new stressor will have on mental health and well-being in order to develop and disseminate appropriate interventions for the general population and for the other at-risk groups.